The Fractal Dimension of River Length Based on the Observed Data - Ni Zhihui; Wu Lichun; Wang Ming-hui; Yi Jing; Zeng Qiang (Journal of Applied Mathematics)
Although the phenomenon that strictly meets the constant dimension fractal form in the nature does not exist, fractal theory provides a new way and means for the study of complex natural phenomena. Therefore, we use some variable dimension fractal analysis methods to study river flow discharge. On the basis of the flood flow corresponding to the waterline length, the river of the overall and partial dimensions are calculated and the relationships between the overall and partial dimensions are discussed. The law of the length in section of Chongqing city of Yangtze River is calibrated by using of variable fractal dimension. The results conclude that it does express a second-order accumulated variable-dimensional fractal phenomenon, and the dimension can reflect the degree of the river; the greater dimension, the more the river bend. It has different dimensions at a different location in the same river. In the same river, the larger dimension, the worse flow discharge capacity of the river and the more obvious of the flood will be on the performance.